Agribusiness and its productive potential towards the bicentennial - Quispe Quezada, Uriel Rigoberto (2021)
The contribution of agribusiness in the face of the bicentennial in Peru, is being represented more and more with greater presence in international markets and the scientific community, for the benefits it offers through crops with high nutritional and food value, rescued in In some cases, due to the appreciable genetic value of the resources found in germplasm banks, in whose species it is vast and the number of accessions and lines is becoming increasingly important, in the uses that are given to them, which contributes options for their industrialization and welcomed by consumers who appreciate its nutritional richness and meet expectations. The objective of the research addresses knowing the multiple potentialities of export crops, promoted through agribusiness in the face of the bicentennial in the country. Regarding the methodology, it addresses taking in reference levels of analysis of how flagship crops have been behaving in international markets supported by the use and systematization of various sources of information, in whose investigative incision it addresses with critical capacity. The conclusions that are presented over decades, the flag crops are having their participation, an expectant place in commercial environments, highlighting their potentialities by presenting nutraceutical richness, which are used as a source of food for human consumption and for instead it places their participation in an increasingly competitive world.